2022
DOI: 10.1101/2022.04.11.22273720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The contribution of genetic risk to the comorbidity of depression and anxiety: a multi-site electronic health records study

Abstract: Importance: Depression and anxiety are common and highly comorbid, posing a clinical and public health concern because such comorbidity is associated with poorer outcomes. Objective: To evaluate association of genetic risk scores with depression and anxiety diagnosis either in isolation or comorbid with each other. Design: International Classification of Diseases (ICD) ninth and tenth edition codes were extracted from longitudinal electronic health records (EHR) from four EHR-linked biobanks with genetic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
2
0
0
Order By: Relevance
“…However, the phenotypic profiles of patients with isolated depression and isolated anxiety differed significantly from those with both depression and anxiety, after adjusting for potential confounders, suggesting that these phenotypes correspond to distinct risk groups. This aligns with a recent genetic study of depression, anxiety, and their comorbidity, which showed independent depression and anxiety polygenic contributions to the comorbidity (Coombes et al, 2022). Relative to prior analyses of epidemiological samples of non-elderly individuals, aged 15-54 years (Kessler et al, 2008(Kessler et al, , 1996, our sample was also older, with a median age of 66.4 years.…”
Section: Discussionsupporting
confidence: 87%
“…However, the phenotypic profiles of patients with isolated depression and isolated anxiety differed significantly from those with both depression and anxiety, after adjusting for potential confounders, suggesting that these phenotypes correspond to distinct risk groups. This aligns with a recent genetic study of depression, anxiety, and their comorbidity, which showed independent depression and anxiety polygenic contributions to the comorbidity (Coombes et al, 2022). Relative to prior analyses of epidemiological samples of non-elderly individuals, aged 15-54 years (Kessler et al, 2008(Kessler et al, , 1996, our sample was also older, with a median age of 66.4 years.…”
Section: Discussionsupporting
confidence: 87%
“…However, the phenotypic profiles of patients with isolated depression and isolated anxiety differed significantly from those with both depression and anxiety suggesting that these phenotypes correspond to distinct risk groups [53]. This aligns with a recent genetic study of depression, anxiety and their comorbidity, which showed independent depression and anxiety polygenic contributions to the comorbidity.…”
Section: Discussionsupporting
confidence: 86%